Medicinal and nutritional evaluation of three species of Unconventional Food Plants (UFPs): A literature review (Research, Society and Development, 2021)
In the last years, the increase in the search for medicinal and nutritional alternatives for introduction into the field of people's health has led to the use of plants in the daily lives of the population. Consequently, several studies aimed to evaluate the potential use of such plants and their health benefits. Therefore, the aim of the study is to conduct a literature review on the potential medicinal and nutritional use of three species present in the southern region of Brazil, namely Rumex crispus, Conyza bonariensis and Taraxacum officinale. Research was carried out in the PubMed, EMBASE, Virtual Health Library (VHL) and Digital Repository databases at the Federal University of Santa Maria, using the previously selected descriptors from the MeSh and DeCs platforms. The searches were carried out in the period of December 2020. The inclusion criteria used included articles from the last 20 years, but literature reviews were excluded. After the searches 27 articles were selected to compose the literature review. Plants are rich in different phytochemicals, which guarantee species with different potential uses, such as antioxidants, anti-inflammatories, anti-diabetics, antimicrobials and anticancer agents. In addition, its uses in food are wide, being found in salads, sauces, jellies or teas. Most plants showed cytotoxic activity against tumor cells, but toxicity against healthy cells was not observed in the studies. Therefore, the medicinal and nutritional potential of the analyzed species is observed, and further studies are needed to elucidate it in clinical practice.